2017
DOI: 10.18632/oncotarget.16076
|View full text |Cite
|
Sign up to set email alerts
|

CCR4 is a determinant of melanoma brain metastasis

Abstract: We previously identified the chemokine receptor CCR4 as part of the molecular signature of melanoma brain metastasis. The aim of this study was to determine the functional significance of CCR4 in melanoma brain metastasis. We show that CCR4 is more highly expressed by brain metastasizing melanoma cells than by local cutaneous cells from the same melanoma. Moreover, we found that the expression of CCR4 is significantly higher in paired clinical specimens of melanoma metastases than in samples of primary tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 40 publications
2
61
0
Order By: Relevance
“…The specific organ microenvironment plays a significant (positive or negative) role in the development of metastasis in that organ . Previous results from our lab showed that brain microenvironmental cells and their molecular products are involved in the progression of melanoma toward brain metastasis …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The specific organ microenvironment plays a significant (positive or negative) role in the development of metastasis in that organ . Previous results from our lab showed that brain microenvironmental cells and their molecular products are involved in the progression of melanoma toward brain metastasis …”
Section: Discussionmentioning
confidence: 89%
“…In our study, we used the brain metastatic variant DP.CB2. Immortalized human microglia‐SV40 cell line (ABM, Milton, ON, Canada) was maintained as described previously . Immortalized human brain microvascular endothelial cells (hCMEC/D3) were kindly provided by Clara Nahmias and Pierre‐Olivier Couraud (Inserm, U1016, Institute Cochin, Paris, France) and were maintained as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…Astrocytic exosome inhibition can prevent BM (41). A multicentre study on 318 patients with breast cancer (84 with BM) highlighted that fibroblast growth factor-inducible protein 14 (FN14) and GRP94 are prediction/prognosis markers that can be used as therapeutic targets in BM patients (42). However, this study was performed in breast cancer patients and the results should be carefully extrapolated in BM from melanoma due to the specific molecular signature of the melanoma cells.…”
Section: Biomarkers In Melanoma Brain Metastasis Predictionmentioning
confidence: 98%
“…During this process, the role of chemokines and their cognate receptors cannot be ignored 91. Izraely discovered that brain‐metastasizing melanoma cells expressed really higher level of C‐C motif chemokine receptor 4 (CCR4).…”
Section: The Mechanism Of Brain Metastasismentioning
confidence: 99%